Diversitas Plankton di Perairan Pantai Sire Kabupaten Lombok Utara - Astriana, Baiq Hilda; Larasati, Chandrika Eka (Program Studi Ilmu Kelautan, Jurusan Perikanan dan Ilmu Kelautan, Fakultas Pertanian, Universitas Mataram, 2021)
Plankton has an important role for aquatic ecosystems, especially in the food network in a waters. This study aims to assess the abundance and diversity index of plankton in Sire Beach, North Lombok Regency. The study was conducted in September 2019 using purposive sampling with 9 sample points. The water sample was filtered using plankton net then put into the sample bottle for identification in the laboratory. Shannon-Wienner Index was used for determining diversity of plankton species. The types of plankton found were 12 genera of phytoplankton from the Bacillariophyta group, including: Biddulphia, Coscinodiscus, Cocconeis, Cylindrotheca, Diploneis, Fragilaria, Gyrosigma, Licmophora, Navicula, Nitzschia, Pleurosigma, and Triceratium. The highest abundance of phytoplankton belonged to Coscinodiscus species as many as 1.380 cells/l at station 2.3. The high abundance of Coscinodiscus might be due to a nutrient supply in these waters. Seagrass ecosystem was thought to have an important role in obtaining nutrients for phytoplankton. Diversity index has a value which ranges between 1.117505-1.841236 showing that it is in the medium category. The uniformity index ranges from 0.450718-0.673373 indicating that the distribution of plankton species in each station is even. The dominance index ranges from 0.233508-0.522215. This shows that there is no type of plankton that dominates the waters of Sire Beach. This is due to the abundance of plankton species at each station which is fairly evenly distributed.